Face to face with wild horses - Momatiuk, Yva, 1940-; Eastcott, John, 1952- (Washington, D.C. : National Geographic, 2009)
The author describes his experiences photographing wild horses, shares what he has learned about the animals, and showcases some of his pictures.
Includes bibliographical references (p. 30) and index.
4.8
3-6
3-6
School Library Journal
Booklist
Keywords: Wild horses -- Juvenile literature; Wild horses -- Pictorial works -- Juvenile literature; Photography of horses -- Juvenile literature; Wild horses; Wild horses -- Pictorial works; Photography of horses; Horses; Horses -- Pictorial works; Photography of horses